Induction of Pluripotency in Adult Equine Fibroblasts without c-MYC. (19th March 2012) - Khodadadi, Khodadad; Sumer, Huseyin; Pashaiasl, Maryam; Lim, Susan; Williamson, Mark; Verma, Paul J.
Abstract : Despite tremendous efforts on isolation of pluripotent equine embryonic stem (ES) cells, to date there are few reports about successful isolation of ESCs and no report of in vivo differentiation of this important companion species. We report the induction of pluripotency in adult equine fibroblasts via retroviral transduction with three transcription factors using OCT4, SOX2, and KLF4 in the absence of c-MYC. The cell lines were maintained beyond 27 passages (more than 11 months) and characterized. The equine iPS (EiPS) cells stained positive for alkaline phosphatase by histochemical staining and expressed OCT4, NANOG, SSEA1, and SSEA4. Gene expression analysis of the cells showed the expression of OCT4, SOX2 NANOG, and STAT3 . The cell lines retained a euploid chromosome count of 64 after long-term culture cryopreservation. The EiPS demonstrated differentiation capacity for the three embryonic germ layers both in vitro by embryoid bodies (EBs) formation and in vivo by teratoma formation. In conclusion, we report the derivation of iPS cells from equine adult fibroblasts and long-term maintenance using either of the three reprogramming factors.